Strategi Pemasaran Keripik Tempe Ceria di Desa Sumber Mulya Kecamatan Simpang Raya Kabupaten Banggai - Ratmi Rosilawati; Dwi Wijayanti; Rengga Lupita Farma (Jurnal Biologi Babasal, 2023)
Abstract: With the advancement of time and creative innovation from humans, tempeh is no longer just a side dish to accompany rice, but can be used as a practical and ready-to-eat snack, namely tempeh chips. The aim of this research is to determine the marketing strategy which includes product, price, promotion and distribution of cheerful tempeh chips in Sumber Mulya Village, Simpang Raya District and its surroundings. This research was carried out at Usaha Ceria, Sumber Mulya Village, Simpang Raya District, Banggai Regency from May to June 2023. The number of samples used was 12 people. The data analysis used is SWOT analysis. The research results show that the product strategy for cheerful tempe chips is that the product is always available, the product has product attributes, brands and labels, and has an affordable price. The promotional strategy for cheerful tempe chips is personal sales promotion, in other words word of mouth promotion. Apart from that, promotions are also carried out through social media. The distribution strategy for cheerful tempe chips is from producers directly to consumers and from producers to distributors and distributors to consumers. Cheerful tempeh chips products are distributed to several shops/supermarkets inside and outside Banggai Regency. Marketing of cheerful tempe chips is in quadrant I supporting an aggressive growth policy (Growth Oriented Strategy).